Tofogliflozin long-term effects on atherosclerosis progression and major clinical parameters in patients with type 2 diabetes mellitus lacking a history of cardiovascular disease: a 2-year extension study of the UTOPIA trial - Katakami, Naoto; Mita, Tomoya; Yoshii, Hidenori; Shiraiwa, Toshihiko; Yasuda, Tetsuyuki; Okada, Yosuke; Kurozumi, Akira; Hatazaki, Masahiro; Kaneto, Hideaki; Osonoi, Takeshi; Yamamoto, Tsunehiko; Kuribayashi, Nobuichi; et al. (Cardiovascular diabetology, 2023)
This study aimed to assess the long-term effects of tofogliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, on atherosclerosis progression and major clinical parameters in patients with type 2 diabetes lacking an apparent history of cardiovascular disease. This was a prospective observational 2-year extension study of the "Using TOfogliflozin for Possible better Intervention against Atherosclerosis for type 2 diabetes patients (UTOPIA)" trial, a 2-year randomized intervention study. The primary endpoints represented changes in the carotid intima-media thickness (IMT). Secondary endpoints included brachial-ankle pulse wave velocity (baPWV) and biomarkers for glucose metabolism, lipid metabolism, renal function, and cardiovascular risks. The mean IMT of the common carotid artery (IMT-CCA) significantly decreased in both the tofogliflozin (- 0.067 mm, standard error 0.009, p < 0.001) and conventional treatment groups (- 0.080 mm, SE 0.009, p < 0.001) throughout the follow-up period; however, no significant intergroup differences in the changes (0.013 mm, 95% confidence interval (CI) - 0.012 to 0.037, p = 0.32) were observed in a mixed-effects model for repeated measures. baPWV significantly increased in the conventional treatment group (82.7 ± 210.3 cm/s, p = 0.008) but not in the tofogliflozin group (- 17.5 ± 221.3 cm/s, p = 0.54), resulting in a significant intergroup difference in changes (- 100.2 cm/s, 95% CI - 182.8 to - 17.5, p = 0.018). Compared to the conventional treatment group, tofogliflozin significantly improved the hemoglobin A1c and high-density lipoprotein cholesterol levels, body mass index, abdominal circumference, and systolic blood pressure. The frequencies of total and serious adverse events did not vary significantly between the groups. Tofogliflozin was not associated with improved inhibition of carotid wall thickening but exerted long-term positive effects on various cardiovascular risk factors and baPWV while showing a good safety profile.